Geographic Information System of Contraceptives Users in Samarinda Seberang Sub-District - Muhammad Renaldi Arianda; Ida Maratul Khamidah; Nia Kurniadin (Politeknik Pertanian Negeri Samarinda, 2021)
Birth Control “Keluarga Berencana” (KB) is a government program designed to balance the needs and population. Birth Control is an attempt to measure the number of children and the desired birth spacing of children. Therefore, the Government launched a program or method to prevent and delay pregnancy. Therefore, the purpose of this study is to create a geographic information system for data collection of contraceptive users based on a website that is useful as a place to store data on contraceptive users and information maps as a benchmark for the achievement of Birth Control instructors in the area of ​​Samarinda opposite. The results of this study that the existence of this geographic information system website, besides being able to assist the public in obtaining information about contraceptives, can also assist the work of Birth Control instructors in the regions, especially in the Samarinda Seberang area in recording Birth Control users in their working areas and as a step to help reduce paper use and modernization from the old system.